Blueberry Polyphenols Increase Nitric Oxide and Attenuate Angiotensin II-Induced Oxidative Stress and Inflammatory Signaling in Human Aortic Endothelial Cells - Rami S. Najjar; Shengyu Mu; Rafaela G. Feresin (MDPI AG, 2022)
Accumulating evidence indicate that blueberries have anti-hypertensive properties, which may be mainly due to its rich polyphenol content and their high antioxidant capacity. Thus, we aimed to investigate the mechanisms by which blueberry polyphenols exert these effects. Human aortic endothelial cells (HAECs) were incubated with 200 µg/mL blueberry polyphenol extract (BPE) for 1 h prior to a 12 h treatment with angiotensin (Ang) II, a potent vasoconstrictor. Our results indicate that Ang II increased levels of superoxide anions and decreased NO levels in HAECs. These effects were attenuated by pre-treatment with BPE. Ang II increased the expression of the pro-oxidant enzyme NOX1, which was not attenuated by BPE. Pre-treatment with BPE attenuated the Ang II-induced increase in the phosphorylation of the redox-sensitive MAPK kinases, SAPK/JNK and p38. BPE increased the expression of the redox-transcription factor NRF2 as well as detoxifying and antioxidant enzymes it transcribes including HO-1, NQO1, and SOD1. We also show that BPE attenuates the Ang II-induced phosphorylation of the NF-κB p65 subunit. Further, we show that inhibition of NRF2 leads to a decrease in the expression of HO-1 and increased phosphorylation of the NF-κB p65 subunit in HAECs treated with BPE and Ang II. These findings indicate that BPE acts through a NRF2-dependent mechanism to reduce oxidative stress and increase NO levels in Ang II-treated HAECs.